Arms Export Controls under Siege of Globalisation: Defeated Nation States or Voluntary Surrender? - Helferich, John N. T. (Tectum Verlag, 2020)
While defence industrial production is increasingly transnationalised, the control of arms exports still takes place almost exclusively on a national level. With the example of the German export control regime, this work analyses if the current situation yields arms export control risks that could undermine German security policy principles. Furhermore, inferences about IR theory are drawn based on the current regulation and its implementation. Looking at three particular case studies, this work finds that transnational production and trade indeed creates a number of arms diversion risks, however, these risks are predominantly a result of political choice rather than a phenomenon of hyper-globalisation. This work contributes to key discourses in International Security.